2015
DOI: 10.14260/jemds/2015/1874
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dry Eye in Post - Menopausal Women

Abstract: Dry eye refers to a heterogeneous group of conditions all characterized by inadequate lubrication of ocular surface. Dry eye is a potentially serious and chronic condition. It may severely limit a person's activity, and in extreme cases cause blindness. Postmenopausal dry eye syndrome has frustrated patients, researchers and clinicians due to the paucity of successful treatment options and difficulty in assessing efficacy of treatment modalities. Hence early detection and treatment is necessary. AIM: This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…M.R. Pujari et al [9] found dry eye to be more common in the 65-75 years age group and more common in rural population. Mohana Majumdar et al [10] studied 293 post-menopausal women and found the common ocular findings were foreign body sensation, grittiness, hyperemia, mucoid discharge and fluctuating or blurry vision.…”
Section: Discussionmentioning
confidence: 98%
“…M.R. Pujari et al [9] found dry eye to be more common in the 65-75 years age group and more common in rural population. Mohana Majumdar et al [10] studied 293 post-menopausal women and found the common ocular findings were foreign body sensation, grittiness, hyperemia, mucoid discharge and fluctuating or blurry vision.…”
Section: Discussionmentioning
confidence: 98%